Advancements and Refinement in Facial Neuromodulators. Issue 4 (October 2016) - Kordestani, Reza; Small, Kevin H.; Rohrich, Rod J.
Abstract : Summary: The use of neuromodulators has increased by approximately 748 percent from 2000 to 2014 and has become an integral adjunct for facial rejuvenation. Knowledge of facial anatomy, accurate facial analysis, and familiarity with neurotoxin characteristics will minimize complications and optimize results. Current U.S. Food and Drug Administration–approved neurotoxins in the United States include onabotulinumtoxin A (Botox), abobotulinumtoxin A (Dysport), and incobotulinumtoxin A (Xeomin). The dosage and effect of these products are not interchangeable, so practitioners should master the utility and response of one product before trying the other products. All products have equivalent success in appropriately trained hands; the senior author (R.J.R.) favors no particular neurotoxin. This article provides a stepwise approach to treat dynamic facial rhytides with neuromodulators, including indications, facial analysis, preparation and injection technique, post-procedure care, and complications. Abstract : Supplemental Digital Content is available in the text.